Anthropometric Measurements to Predict NICU Admission for Infants of Diabetic Mothers - Celik, Fatma Cakmak; Aygun, Canan; Tumer, Guzin; Kucukoduk, Sukru; Bek, Yuksel (Bangladesh Journal of Medical Science, 2022)
Aim: Can NICU admission of IDM be predicted by anthropometric measurements like birth weight, lenght, head circumference (HC), mid upper arm circumference (MUAC) or triceps skin fold thickness (TSFT). Method: Eighty-six-term IDMs were analyzed prospectively. MUAC, HC and TSFT were measured within 48 hours of life. Prenatal-natal-postnatal problems; NICU admission; maternal characteristics, HbA1c were recorded. Results: Mean birth weight, gestational age were 3453.3±582.4g and 38.0±0.97weeks. 63.9% of IDMs was admitted to NICU. 56.3% hospitalized due respiratory problems; 32,7 % required endotracheal intubation. Mean MUAC, TSFT, HC and MUAC/HC ratio were 11.2±1.1 cm, 7.1±2.2 mm, 35.0±1.8 cm and 0.32±0.03 cm respectively for all. Although there was no significant relation between NICU admission and MUAC (p=0.071), TSFT and MUAC/HC were significantly higher in babies admitted to NICU (p=0.006 for TSFT, p<0.001 for MUAC/HC). HC was significantly low in babies followed in NICU (P<0.001). With increment of TSFT, MUAC/HC and HbA1c, NICU admission increases positively, but HC affects NICU admission negatively (OR for TSFT:1.6, OR for MUAC/HC: 2.1, OR for HbA1c: OR for HC:0,3). Mechanic ventilation requirement is affected positively by TSFT (p=0.008, OR:1.5) and affected negatively by HC (p=0.004, OR:0.6). Conclusion: This preliminary study showed; TSFT, HC and MUAC/HC ratio are helpful criterias to predict NICU admission risk for IDMs and might be helpful for risk assesment in limited settings. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 72-78